Phenolic signals for prehaustorium formation in Striga hermonthica - Aoki, Natsumi; Cui, Songkui; Ito, Chiharu; Kumaishi, Kie; Kobori, Shungo; Ichihashi, Yasunori; Yoshida, Satoko (Frontiers in Plant Science, 2022)
Striga hermonthica is a root parasitic plant that causes considerable crop yield losses. To parasitize host plants, parasitic plants develop a specialized organ called the haustorium that functions in host invasion and nutrient absorption. The initiation of a prehaustorium, the primitive haustorium structure before host invasion, requires the perception of host-derived compounds, collectively called haustorium-inducing factors (HIFs). HIFs comprise quinones, phenolics, flavonoids and cytokinins for S. hermonthica; however, the signaling pathways from various HIFs leading to prehaustorium formation remain largely uncharacterized. It has been proposed that quinones serve as direct signaling molecules for prehaustorium induction and phenolic compounds originating from the host cell wall are the oxidative precursors, but the overlap and distinction of their downstream signaling remain unknown. Here we show that quinone and phenolic-triggered prehaustorium induction in S. hermonthica occurs through partially divergent signaling pathways. We found that ASBr, an inhibitor of acetosyringone in virulence gene induction in the soil bacterium Agrobacterium, compromised prehaustorium formation in S. hermonthica. In addition, LGR-991, a competitive inhibitor of cytokinin receptors, inhibited phenolic-triggered but not quinone-triggered prehaustorium formation, demonstrating divergent signaling pathways of phenolics and quinones for prehaustorium formation. Comparisons of genome-wide transcriptional activation in response to either phenolic or quinone-type HIFs revealed markedly distinct gene expression patterns specifically at the early initiation stage. While quinone DMBQ triggered rapid and massive transcriptional changes in genes at early stages, only limited numbers of genes were induced by phenolic syringic acid. The number of genes that are commonly upregulated by DMBQ and syringic acid is gradually increased, and many genes involved in oxidoreduction and cell wall modification are upregulated at the later stages by both HIFs. Our results show kinetic and signaling differences in quinone and phenolic HIFs, providing useful insights for understanding how parasitic plants interpret different host signals for successful parasitism.